Analisis Pengaruh Sikap, Subjective Norm dan Perceived Behavioral Control Terhadap Purchase Intention Pelanggan SOGO Department Store di Tunjungan Plaza Surabaya - Jessvita Anggelina Jaya Pratana (Jurnal Strategi Pemasaran, 2014)
The purpose of this research study is to know about attitude, subjective norm and perceived control influencer towards purchasing intention of SOGO department store customers in Tunjungan plaza Surabaya. The type of this research is causal research. This research samples takes among peoples that have bought goods from SOGO department store Tunjungan Plaza Surabaya. The sampling technique are non probability sampling using purposive sampling. The analysis technique is using multiple linier regression. The result of this research shows that attitude, subjective norm and behavioral control influence simultaneously and partially towards customers will’s to buy in SOGO department store in Tunjungan Plaza Surabaya, and behavioral control compare with attitude and subjective norm.